Pseudopodosira boltovskoyi sp. nov. (Pseudopodosiraceae, Bacillariophyta) from coastal waters of Argentina. Issue 3 (1st May 2017) - Sar, Eugenia A.; Lavigne, Andrea S.; Wetzel, Carlos E.; Ector, Luc; Sunesen, Ines
Abstract: A new extant marine diatom, Pseudopodosira boltovskoyi sp. nov . (Pseudopodosiraceae, Bacillariophyta), is described with light and scanning electron microscopy from Argentinean coastal waters. Pseudopodosira boltovskoyi sp. nov . is morphologically distinct with the following combination of characters: (1) cells with numerous lenticular chloroplasts; (2) frustules commonly heterovalvate; (3) valves with concave central area generally occupied by one to several bulges, rarely without bulges; (4) oblique striae located on a horizontal, convex shelf of the valve surface; (5) valve mantle unperforated internally and with variable number of rimmed pores located below the flange externally; (6) one ring of rimoportulae irregularly spaced, not visible externally. Pseudopodosira calyciflos (Tempère & Brun) is formally designated as the generitype, and a new name Pseudopodosira jouseana nom. nov . is proposed to replace for Pseudopodosira pileiformis based on the fact that the protologue quoted the former taxon as a synonym of the latter. We compare the new species with the morphologically allied extinct species Pseudopodosira modesta, P. wittii, P. bella, P. westii, P. hyalina and P. himilis . Although most species of Pseudopodosira are extinct, P. westii, P. calyciflos and P. echinus were recorded as extant. Nevertheless, the survival of P. westii on European coastal sediments is problematic. Pseudopodosira calyciflos was only mentioned in the protologue as living in the Hawaiian Islands but is illustrated by a figure that only shows one valve. As far as we can determine, P. echinus and Pseudopodosira boltovskoyi sp. nov . are the only extant species.